2022
DOI: 10.1136/rmdopen-2022-002693
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of certolizumab pegol in uveitis due to immune-mediated inflammatory diseases: multicentre study of 80 patients

Abstract: ObjectivesTo evaluate effectiveness and safety of certolizumab pegol (CZP) in uveitis due to immune-mediated inflammatory diseases (IMID).MethodsMulticentre study of CZP-treated patients with IMID uveitis refractory to conventional immunosuppressant. Effectiveness was assessed through the following ocular parameters: best-corrected visual acuity, anterior chamber cells, vitritis, macular thickness and retinal vasculitis. These variables were compared between the baseline, and first week, first, third, sixth mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A multicenter clinical trial studied its safety and efficacy in 80 patients with uveitis due to immune-mediated inflammatory diseases after CZP treatment, this study found that CZP is effective in improving visual acuity, ocular inflammation, and macular thickness; it also found that the median dose of glucocorticoids decreased after CZP use compared to before. This study revealed that CZP is safe and effective in the treatment of uveitis caused by different immune-mediated inflammatory diseases [57].…”
Section: Certolizumab Pegol (Czp)mentioning
confidence: 71%
“…A multicenter clinical trial studied its safety and efficacy in 80 patients with uveitis due to immune-mediated inflammatory diseases after CZP treatment, this study found that CZP is effective in improving visual acuity, ocular inflammation, and macular thickness; it also found that the median dose of glucocorticoids decreased after CZP use compared to before. This study revealed that CZP is safe and effective in the treatment of uveitis caused by different immune-mediated inflammatory diseases [57].…”
Section: Certolizumab Pegol (Czp)mentioning
confidence: 71%
“…AZA, Azathioprine; bDMARDs, biologic DMARDs; cDMARDs, conventional DMARDs; DMARD, disease modifing antirheumatic drug; HCQ, hydroxychloroquine; IVIG, intravenous immunoglobulin; LTBI, latent tuberculosis infection; MTX, methotrexate; NSAIDs, nonsteroidal anti-inflammatory drugs; PRSA, poststreptococcal reactive arthritis; SSZ, sulfasalazine; TNFi, tumor necrosis factor inhibitor; tsDMARD, targeted synthetic DMARDs.aMTX is used first line for ocular inflammation related to reactive arthritis. Severe ocular inflammation refractory to methotrexate may require additional therapies, such as cyclosporine, etanercept, certolizumab, azathioprine, mycophenolate mofetil, cyclophosphamide, or IVIG [22,23].bIf there is evidence of cardiac involvement, then the patient should be reclassified as acute rheumatic fever and continue receiving secondary prophylaxis per American Heart Association guidelines [42].cCombination of SSZ and infliximab was used in a patient who later developed peripheral and axial psoriatic arthritis after PSRA diagnosis.dIntraarticular steroids may be effective second-line treatment in children [62,63], but intraarticular steroids delays resolution of arthritis in adults, especially if given during initial antibiotic course [49,64,65].eHCQ in contraindicated in Child–Pugh–Turcotte classification C.fSSZ is contraindicated in Child–Pugh–Turcotte classification B or C.…”
Section: Discussionmentioning
confidence: 99%
“…aMTX is used first line for ocular inflammation related to reactive arthritis. Severe ocular inflammation refractory to methotrexate may require additional therapies, such as cyclosporine, etanercept, certolizumab, azathioprine, mycophenolate mofetil, cyclophosphamide, or IVIG [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pegylated humanised Fab Yes Improved control in open-label and retrospective clinical studies 242,243 and decreased acute anterior uveitis recurrence in phase IV clinical study of treatment for spondyloarthritis. 244…”
Section: Certolizumabmentioning
confidence: 99%